2021
DOI: 10.3390/ijms221910192
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Cardiovascular Disease Risk Profile in Children and Adolescents with Type 1 Diabetes

Abstract: Cardiovascular disease (CVD) is the primary cause of higher and earlier morbidity and mortality in people with type 1 diabetes (T1D) compared to people without diabetes. In addition, women with T1D are at an even higher relative risk for CVD than men. However, the underlying pathophysiology is not well understood. Atherosclerotic changes are known to progress early in life among people with T1D, yet it is less clear when excess CVD risk begins in females with T1D. This review explores the prevalence of classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 240 publications
(299 reference statements)
0
10
0
Order By: Relevance
“…Hormonal causes, worse glycaemic control in females than males, especially during adolescence, psychosocial factors, and CVRFs have been implicated. 29 In this study, girls had a higher prevalence of obesity than boys, which probably contributed to this difference. However, it should be underlined that boys had higher SBP in our cohort than girls, which is consistent with BP normalcy tables showing higher BP values in boys.…”
Section: Cvrfs According To Age and Bp Statusmentioning
confidence: 55%
See 3 more Smart Citations
“…Hormonal causes, worse glycaemic control in females than males, especially during adolescence, psychosocial factors, and CVRFs have been implicated. 29 In this study, girls had a higher prevalence of obesity than boys, which probably contributed to this difference. However, it should be underlined that boys had higher SBP in our cohort than girls, which is consistent with BP normalcy tables showing higher BP values in boys.…”
Section: Cvrfs According To Age and Bp Statusmentioning
confidence: 55%
“…In this study, female patients had a higher prevalence of accumulated risk factors than male patients. Other studies have also shown that girls with T1D have a higher prevalence of individual CVRFs compared with boys, although it is less clear when excess cardiovascular risk begins in female patients with T1D 29,30 . A study in Australia showed that young female participants with T1D had higher SBP, DBP, cholesterol, and albumin excretion rate than male participants, together with a higher risk of developing CVD 31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with healthy controls, the ASCVD mortality ratio for people with type 1 diabetes was 40-fold in women and 10-fold in men—a difference that starts as early as in childhood and adolescence 90 and was not fully attributable to differences in traditional risk factors or glycemic management. 90,135 In people with RA, several studies have established that men have a greater burden of traditional ASCVD risk factors than women, 136,137 while women are at greater risk for left ventricular hypertrophy than men with an odds ratio of 6.56 (95% CI, 1.34–30.96) after controlling for CVD risk factors. 91 In one study, women <40 years old had the same ASCVD event rate as age-matched men, although men versus women in all older age groups had a greater event rate.…”
Section: Ascvd Pathogenesis In Specific Immune Disordersmentioning
confidence: 92%